Two-dose seasonal influenza vaccine coverage and timeliness among children aged 6 months through 3 years: An evidence from the 2010–11 to the 2014–15 seasons in Zhejiang province, east China. Issue 1 (2nd January 2017) - Hu, Yu; Chen, Yaping; Zhang, Bing
ABSTRACT: Objective : To evaluate the coverage and timeliness of seasonal influenza vaccine vaccination (SIV) among children aged 6 months to 3 years from the 2010–11 through the 2014–15 seasons. Methods : Children registered in Zhejiang Provincial Immunization Information System (ZJIIS) and needed 2 seasonal influenza vaccine doses in a given season from 2010–11 to 2014–15 were enrolled. Socio-economic information and SIV records of target children were extracted from ZJIIS on 1 January 2016. Any (≥1 dose) and full (2 doses) vaccination coverage by December 1 and March 31 as well as interval between 2 doses were calculated. Trends of coverage over time and determinants on fully vaccination coverage and interval between 2 doses were assessed. Results : Full SIV overage by Mar 31 increased from the 2010–11 to the 2014–15 seasons (2.60% vs 2.92%). Less than 1% of children received 2 doses by December 1. The interval between 2 doses among fully vaccinated children decreased over time (2010–11: 68.32 days; 2014–15: 49.51 days; p < 0.05). Age, socio-economic development level of resident areas were inversely associated with full vaccination coverage and resident children had a significantly higher full vaccination coverage. Younger age, resident children, receiving vaccination from higher service frequency clinics and clinics with morning and afternoon sessions were positive determinants of a shorter interval between 2 doses. Conclusion : Majority of children aged 6 months to 3 years remained at risk of incomplete and delayed SIV. The importance of the 2-dose SIV recommendation needs to be emphasized and effective interventions needs to be implemented to improve the completeness and the timeliness of SIV.